Transfer of Learning Transformed. (13th February 2013) - Larsen‐Freeman, Diane
Abstract : Instruction is motivated by the assumption that students can transfer their learning, or apply what they have learned in school to another setting. A common problem arises when the expected transfer does not take place, what has been referred to as the inert knowledge problem. More than an academic inconvenience, the failure to transfer is a major problem, exacting individual and social costs. In this article, I trace the evolution of research on the transfer of learning, in general, and on language learning, in particular. Then, a different view of learning transfer is advanced. Rather than learners being seen to "export" what they have learned from one situation to the next, it is proposed that learners transform their learning. The article concludes by offering some suggestions for how to mitigate the inert knowledge problem from this perspective.